How close can we get to the classical magnetotelluric sounding? - Calderón-Moctezuma, Armando; Gómez Ávila, Marianggy Del Carmen; Gomez-Treviño, E.; Yutsis, V.; Guevara-Betancourt, R. (2022)
The classical magnetotelluric (MT) sounding can be defined as data that are invariant under rotation of coordinates -a feature we call centrality- and are affected solely by electromagnetic induction effects –a feature we call all-induction. The classical sounding can be realized only in the case of laterally isotropic media and perfectly horizontal layering. However, in general it is possible to process data from several sites to make an approximation. For instance, the electromagnetic array profiling (EMAP) method addresses the issue of all-induction by means of spatial filtering. The method is very effective but its application is not practical for long profiles because it requires too many contiguous dipoles. A more practical version exists that does not require contiguous dipoles but neither of them addresses the centrality issue; in the first case because the data are taken along a single direction, and in the other because it uses traditional orthogonal modes. In this work we improve over the last approach by introducing centrality to make the approximation closer to the classical sounding. We use the determinant of the impedance tensor, which is the only invariant among all that are known that can handle centrality, the galvanic distortions and also the isolation of all-induction effects through two-dimensional inversion. This approach to the classical MT sounding is illustrated using the synthetic dataset COPROD2S2 and the field dataset BC87 from British Columbia, Canada, which are commonly used for testing new ideas. We also apply it to a recent profile over the Colima Graben, México. Keywords: Magnetotelluric; all-induction; determinant; COPROD2S2; BC87; classical MT sounding.